Analysis of the Distribution of DHF Using Information System Studies Geographical District Karanganyar - Raihan Dicky Ardiansyah; Sinta Novratilova; Wahyu Wijaya Widiyanto (Journal Health Information Management Indonesian (JHIMI), 2024)
Abstract — Dengue Hemorrhagic Fever is still a major public health problem in Indonesia. DHF is closely relatedto geographical/spatial aspects because one of the sources of disease occurrence cannot be separated fromenvironmental factors so that these environmental factors can be mapped using GIS tools. GIS is a spatialdescription of the spread of DHF on the earth's surface that can be displayed in digital graphic form and can bevisualized in map form. This study uses a descriptive analytic survey search method with a spatial approach toanalyze the pattern of distribution of cases, which is then buffered to see the direction of mosquito travel, anddisplays an overlay map. Results The distribution of dengue fever cases in Karangayar sub-district, namely Gedongsub-district had 6 cases, Bejen sub-district 35 cases, Delingan sub-district 17 cases, Gayamdompo sub-district 4cases, Popongan sub-district 34 cases, Tegalgede sub-district 26 cases, Jantiharjo sub-district 27 cases, Bolongsub-district 9 cases, Karanganyar sub-district 13 cases, Cangakan sub-district 34 cases, Jungke sub-district 7 cases,Lalung sub-district 34 cases.